Mode of Vaginal Delivery: A Modifiable Intrapartum Risk Factor for Obstetric Anal Sphincter Injury - Marta Simó González; Oriol Porta Roda; Josep Perelló Capó; Ignasi Gich Saladich; Joaquim Calaf Alsina (Hindawi Limited, 2015)
The aim of this study was to analyze the comparative risks of this anal sphincter injury in relation to the type of intervention in vaginal delivery. We performed an observational, retrospective study of all vaginal deliveries attended at a tertiary university hospital between January 2006 and December 2009. We analyzed the incidence of obstetric anal sphincter injury for each mode of vaginal delivery: spontaneous delivery, vacuum, Thierry spatulas, and forceps. We determined the proportional incidence between methods taking spontaneous delivery as the reference. Ninety-seven of 4526 (2.14%) women included in the study presented obstetric anal sphincter injury. Instrumental deliveries showed a significantly higher risk of anal sphincter injury (2.7 to 4.9%) than spontaneous deliveries (1.1%). The highest incidence was for Thierry spatulas (OR 4.804), followed by forceps (OR 4.089) and vacuum extraction (OR 2.509). The type of intervention in a vaginal delivery is a modifiable intrapartum risk factor for obstetric anal sphincter injury. Tearing can occur in any type of delivery but proportions vary significantly. All healthcare professionals attending childbirth should be aware of the risk for each type of intervention and consider these together with the obstetric factors in each case.